The Harmonious Communication Model on Among Religious Adherents in Sorong, West Papua - Ali Nurdin; Pudji Rahmawati; Sulhawi Rubba (Jurnal Pekommas, 2020)
This research objective is to describe the process and model of harmonious communication among religious adherents and the supporting and inhibiting factors for the occurrence of harmonious communication in Sorong, West Papua. This research uses a qualitative approach with descriptive research to understand the process and model of communication between religious adherents. The research subject of interfaith leaders in Sorong amounted to 7 informant. The data collection method was done by interview and documentation techniques.  Furthermore, the research result is a description of the process of harmonious communication among religious adherents carried out through the stages of structuring harmony and productivity. While, the stages of structuring harmony are carried out through the process of instilling mutual understanding, tolerance, and mutual respect among the adherents of the religion. The steps have resulted in productivity, namely; the realization of harmony among religious communities, and rised to a harmonious communication model that was built based on peace, tolerance, and cooperation. Supporting factors for harmonious communication are the role of the "Forum on Religious Harmony" (FKUB) and the role of religion and culture.  The factor of inhibiting is the existence of socio-economic inequality and ineffective communication between local leaders and communities and national leaders.